Polyamines directly promote antizyme-mediated degradation of ornithine decarboxylase by the proteasome - R. Roshini Beenukumar; Daniela Gödderz; R. Palanimurugan; R. Jürgen Dohmen (Microbial Cell, 2015)
Ornithine decarboxylase (ODC), a ubiquitin-independent substrate of the proteasome, is a homodimeric protein with a rate-limiting function in polyamine biosynthesis. Polyamines regulate ODC levels by a feedback mechanism mediated by ODC antizyme (OAZ). Higher cellular polyamine levels trigger the synthesis of OAZ and also inhibit its ubiquitin-dependent proteasomal degradation. OAZ binds ODC monomers and targets them to the proteasome. Here, we report that polyamines, aside from their role in the control of OAZ synthesis and stability, directly enhance OAZ-mediated ODC degradation by the proteasome. Using a stable mutant of OAZ, we show that polyamines promote ODC degradation in Saccharomyces cerevisiae cells even when OAZ levels are not changed. Furthermore, polyamines stimulated the in vitro degradation of ODC by the proteasome in a reconstituted system using purified components. In these assays, spermine shows a greater effect than spermidine. By contrast, polyamines do not have any stimulatory effect on the degradation of ubiquitin-dependent substrates.